Comparison of short-term (saliva) and long-term (hair) cortisol levels in out-patients with melancholic and non-melancholic major depression. Issue 3 (May 2020) - Herane-Vives, Andrés; Young, Allan H.; Wise, Toby; Aguirre, Juan; de Angel, Valeria; Arnone, Danilo; Papadopoulos, Andrew; Cleare, Anthony J.
Abstract : Background: Major depressive episodes (MDEs) show diverse cortisol level alterations. Heterogeneity in symptom profiles, symptom severity and cortisol specimens may explain these heterogeneous results. Less severely ill out-patients with a non-melancholic MDE (NM-MDE) may have a variation in the rhythm of cortisol secretion rather than in its concentration. Method: Cortisol measures were taken (a) over a short-term period (12 h) by measuring daily salivary output using the area under the curve with respect to the ground (AUCg) and (b) over a long-term period (3 months) in hair. Additionally, cortisol reactivity measures in saliva – the cortisol awakening response and the 30 min delta cortisol secretion after awakening (DELTA) – were investigated in 19 patients with a melancholic MDE (M-MDE) and 52 with a NM-MDE, and in 40 matched controls who were recruited from the UK and Chile. Depression severity scores were correlated with different cortisol measures. Results: The NM-MDE group showed a decreased AUCg in comparison with controls ( P = 0.02), but normal cortisol reactivity and long-term cortisol levels. The M-MDE group did not exhibit any significant cortisol alterations nor an association with depression severity scores. Higher Hamilton Rating Scale for Depression score was linked with decreased hair cortisol concentration (HCC, P = 0.05) and higher DELTA ( P = 0.04) in NM-MDEs, whereas decreased HCC was the sole alteration associated with out-patients with severe M-MDEs. Conclusions: The contrasting short- and long-term cortisol output results are compatible with an alteration in the rhythm of cortisol secretion in NM-MDEs. This alteration may consist of large and/or intense episodes of hypercortisolaemia in moderate NM-MDEs and frequent, but brief and sharp early-morning DELTAs in its severe form. These changes may reflect the effects of environmental factors or episodes of nocturnal hypercortisolaemia that were not measured by the short-term samples used in this study.